Clinical Characteristics of Patients With Abnormal Ocular/Cervical Vestibular Evoked Myogenic Potentials in the Presence of Normal Caloric Responses. (June 2015) - Iwasaki, Shinichi; Fujimoto, Chisato; Kinoshita, Makoto; Kamogashira, Teru; Egami, Naoya; Yamasoba, Tatsuya
Objective: To investigate the clinical features and vestibular symptoms of patients with abnormal ocular vestibular evoked myogenic potentials (oVEMPs) and/or cervical VEMPs (cVEMPs) in the presence of normal caloric responses. Study Design: Retrospective chart review. Setting: Tertiary referral center. Methods: One thousand five hundred twenty-one consecutive patients with balance problems who underwent the caloric, cVEMP, and oVEMP tests were included, and patients who showed abnormal oVEMPs and/or cVEMPs in the presence of normal caloric responses were selected. Clinical characteristics, diagnoses, and vestibular symptoms of the patients were analyzed. Results: Of the 1521 patients, 227 (15%) were found to have abnormal oVEMPs and/or cVEMP responses with normal caloric responses. Benign paroxysmal positional vertigo (BBPV), Meniere's disease, and vestibular migraine were the common diagnoses of these patients. Eighty-one patients (36%) could not be diagnosed with a recognizable disease. Multiple episodes of spinning vertigo with a duration of seconds to hours were their most common vestibular symptoms. Conclusion: BPPV, Meniere's disease, and vestibular migraine are the most frequent diagnoses showing abnormal oVEMP and/or cVEMPs without canal paresis. Apart from these clinical entities, a portion of undiagnosed patients with multiple episodes of vertigo might have a disease that involves the otolith organs only.